Protection of images by combination of vernam stream cipher, AES and LSB steganography in a video clip - Marwah Kamil Hussein; Haleh Amintoosi (Bulletin of Electrical Engineering and Informatics, 2023)
Visual communication has become more popular in recent years, and because data must be transferred safely over a restricted bandwidth, techniques of data security and preservation, such as masking and encryption, have to be included after the optimization process for the image in question. The two most common methods of data protection are encryption and steganography. Steganography is a way for covering data that is hidden in another medium without leaving any proof of the data being changed, whereas cryptography converts regular data into incomprehensible data, which is known as scrambled data. Using the least significant bit (LSB) technique, the information was scrambled with graphics. The Vernam encryption algorithm and the advanced encryption standard (AES) will have a side in the proposed method in the encryption step, and the three improvement proposals using quality standards and encryption will be compared with the Vernam encryption algorithm and the AES encryption algorithm, and the effect of the improvement ratio and the size of the encrypted data with different threshold values will be investigated.